The perceptual cognitive processes underpinning skilled performance in volleyball: - Afonso, J.; Garganta, J.; McRobert, A.; Williams, A. M.; Mequita, I. (Journal of Sports Science & Medicine, 2012)
An extensive body of work has focused on the processes underpinning perceptual-cognitive expertise. The majority of researchers have used film-based simulations to capture superior performance. We combined eye movement recording and verbal reports of thinking to explore the processes underpinning skilled performance in a complex, dynamic, and externally paced representative volleyball task involving in situ data collection. Altogether, 27 female volleyball players performed as centre backcourt defenders in simulated sessions while wearing an eye-tracking device. After each sequence, athletes were questioned concerning their perception of the situation. The visual search strategies employed by the highly-skilled players were more exploratory than those used by skilled players, involving more fixations to a greater number of locations. Highly-skilled participants spent more time fixating on functional spaces between two or more display areas, while the skilled participants fixated on the ball trajectory and specific players. Moreover, highly-skilled players generated more condition concepts with higher levels of sophistication than their skilled counterparts. Findings highlight the value of using representative task designs to capture performance in situ.